Immune Status of Hepatitis B Virus among Vaccinated Hemodialysis Patients - Syed Ali Raza, Sohail Hussain, Faiza Nafees Khan, Imtiaz Begum, Santosh Kumar Sidhwani, Madeeha Sadiq (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To check immune status of hemodialysis patients with vaccination history at a tertiary care hospital to Hepatitis B virus. Methods: Study design was cross sectional study which was conducted in Department of Medicine, Ziauddin University, Karachi from May 2011 till November 2011. One hundred and three patients were included in this study who matched the inclusion criteria after taking their informed consent. Data analysis was done by SPSS version 12. Results: The study comprised of male subjects 69(67%) and female patients were 34(33%). The mean age was 51.1 years and standard deviation age was ±14.3 years, the post vaccination duration was recorded and had a mean value of 7.6±0.9 months, mean value of anti HBs antibody level was 184.6±293.4 and the mean duration for hemodialysis was 26.4±12 months. 37(35.9%) of the patients were non-responders, while 19(18.4%) were weak responders and high responders comprised most of study sample i.e. 47(45.6%). Hemodialysis schedule of patients varied with 70(68%) had dialysis twice weekly as compared to this 33(32%) patients had hemodialysis schedule of thrice weekly. Conclusion: this was a preliminary study which showed a very high immunization response by hepatitis-B vaccine among patients on hemodialysis that neither correlated with age, systemic inflammation nor nutritional status.